Researching English in contemporary China - Bolton, Kingsley (2015)
This article provides and introduction to the range of research issues covered by the contributions to this special issue on English in contemporary China. It is suggested that the role of English in Chinese society today cannot be considered in isolation from the sociolinguistic background, as well as the social and political context of contemporary Chinese society. With reference to the present-day sociolinguistic dynamics of China, an important issue is the current spread of Putonghua as the national language across the nation, a process linked to the demands and exigencies of the state education system. With reference to the spread of English, one continuing issue is the relationship between the learning of English, and the actual use of the language. In this context, it is relevant to consider that, in recent decades, official policies to the language have drawn their motivation from both economic and political considerations, where various ideologies have played a role.